The Quality of Direct Procedures in Students’ Indonesian Translation of English Folklore Drama Scripts - Abdul Gani, Citra Amiliani (English Education Journal, 2019)
According to Vinay and Darbelnet (1995), direct translation refers to the transposition of source language message element by element into target language based on either structural parallelism or metalinguistic parallelism. However, both parallelisms are not realized by the student translators so that sometimes they apply inappropriate direct translation. Therefore, this study is aimed to assess the quality of students’ direct translation procedures according to Larson (1994) in Indonesian rendering of English folklore drama script. This study employed descriptive qualitative method with the involvement of respondents for quality assessment. The result reveals that 445 direct procedures consisting of 45 borrowing translations, 18 calque translations, and 382 literal translations produce 249 accurate, 64 sufficiently accurate, and 132 less accurate translations. Dealing with clarity, 314 are considered as clear, 71 sufficiently clear, and 60 less clear translations. In addition, the analysis of naturalness results 285 natural, 51 sufficiently natural, 58 less natural, and 51 unnatural translations. The problems derived from students’ direct procedures are the use of unacceptable loan word and word by word translation which can create misinterpretation. Therefore, the students should increase their awareness of the structural and metalinguistic parallelisms between source and target language.